2014
DOI: 10.1103/physreve.90.013010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic interaction of microswimmers near a wall

Abstract: The hydrodynamics of an archetypal low-Reynolds number swimmer, called “squirmer”, near a wall has been numerically studied. For a single squirmer, depending on the swimming mechanism, three different modes are distinguished: (a) the squirmer escaping from the wall, (b) the squirmer swimming along the wall at a constant distance and orientation angle, and (c) the squirmer swimming near the wall in a periodic trajectory. The role of inertial effects on the near-wall motion of the squirmer is quantified. The dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
171
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(186 citation statements)
references
References 64 publications
15
171
0
Order By: Relevance
“…The squirmer model has also been employed to study the effects of the hydrodynamic near field on the swimming motion near surfaces [44,45].…”
Section: Hydrodynamic Interactions Of Microswimmers With Surfaces 31mentioning
confidence: 99%
“…The squirmer model has also been employed to study the effects of the hydrodynamic near field on the swimming motion near surfaces [44,45].…”
Section: Hydrodynamic Interactions Of Microswimmers With Surfaces 31mentioning
confidence: 99%
“…Accordingly, numerical and analytical simulations report mostly on two-dimensional (2D) systems: either rigorous 2D geometries [12][13][14][15], or the change in rotational diffusion properties in pure Brownian particles with varying degrees of freedom [16], or zconfined quasi-2D disks or rods with coupled hydrodynamic interactions [17][18][19][20][21]14], or swimmers confined to two dimensions interacting by three-dimensional hydrodynamic fields [22]. In the case of full three-dimensional (3D) systems, numerical simulations either exclude hydrodynamic interactions [23,24] or are restricted to small system sizes [25]. In experimental studies, various artificial systems have been reported on, each showing interesting individual features.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most basic types of interaction is the scattering off a solid plane. Bacteria and other microswimmers with rearmounted flagella ("pusher" type) are well known to accumulate spontaneously on planar surfaces [12], a phenomenon that has been equally well explained by theories based on either purely steric [7] or hydrodynamic [6,13] interactions. New experiments are finally prising these two effects apart, with results in clear support of the latter [14,15].…”
mentioning
confidence: 99%
“…Qualitatively, m ≠ 1 signals an interaction. Theoretical studies based on far-field hydrodynamics for puller microswimmers skimming off planar and spherical surfaces [13,[21][22][23] predict consistently a repulsive reorientation of the microorganism's trajectory. Indeed, this can be directly observed from the angular deflection βðθ in Þ measured in our experiments (Fig.…”
mentioning
confidence: 99%